Efeito da terapia fotodinâmica sobre biofilme de Enterococcus faecalis e estrutura dentinária - Alves, Denise Ramos Silveira (2016)
Objective: Evaluate the effect of photodynamic therapy (PDT) on Enterococcus faecalis biofilm in infected root canals and on dentin structure. Methods: Twenty-one root canals of a sample of 24 extracted single-rooted human teeth were infected by E. faecalis for 60 days to form biofilm. The antimicrobial strategies tested were (n=3 in each group): root canal preparation using NiTi rotary instruments, 2.5% NaOCl and 17% EDTA irrigation, and PDT with 0.01% methylene blue (group I) or 0.01% malachite green (group II); root canal preparation using NiTi rotary instruments, 2.5% NaOCl and 17% EDTA irrigation, and PDT with 0.01% methylene blue (group III); PDT with 0.01% methylene blue without root canal preparation (group IV); root canal preparation using NiTi rotary instruments, 22.5% NaOCl and 17% EDTA irrigation, and no PDT (group V); 2.5% NaOCl irrigation with no root canal preparation, and 17% EDTA irrigation (group VI); positive control (group VII). Three roots were not infected and were used as negative controls (group VIII). Samples for microbiological tests were collected using three sterile paper points, later stored in BHI and incubated at 37o C for 48 hours at three time points: before (S1) and after (S2) root canal preparation, and after PDT application (S3). Bacterial growth was analyzed according to turbidity of culture medium, presence of bacteria, and spectrophotometric optical density (nm). Specimens were sectioned and prepared for SEM analysis of dentin structure. Results: Bacteria were found at S1, S2 and S3 in all experimental groups. Optical density of culture media at S2 and S3 in groups I, II and III were lower than at S1, but not statistically different. Optical density of culture media at S2 was 28.70% and 24.67% lower than at S1 in groups I and II; after PDT, optical density was 90.00% (group I) and 37.30% (group II) lower. In group III, it was 97.70% lower at S2 and an additional 92.00% lower after PDT. In group IV, optical density increase 3.2%. Dentin analysis after PDT revealed areas of melting and recrystallization, peritubular dentin projections, intertubular dentin erosion and fusion of dentinal tubule openings, which made dentin surface irregular. Some dentinal tubules were obliterated, and there were changes in the shape of their openings. Conclusion: PDT applied after root canal preparation using manual or rotary files was not effective in eliminating E. faecalis completely. PDT changed dentin structure and resulted in dentin melting and recrystallization, as well as in dentinal tubule erosion and obliteration.